Novel Strategies to Treat Hepatic Steatosis and Steatohepatitis. Issue 9 (25th July 2019) - Perry, Rachel J.
Abstract : Concordant with soaring obesity rates, nonalcoholic fatty liver disease (NAFLD) has become the most common chronic liver disease in the world. The obesity epidemic demands interventions to reverse obesity‐associated hepatic steatosis, NAFLD, and nonalcoholic steatohepatitis, and several new pharmacologic approaches have been developed within the past several years. Steatosis develops when energy delivery to the liver, modulated by rates of hepatic lipogenesis, exceeds the capacity of the liver to utilize or export this energy. Therefore, pharmacologic approaches to reverse hepatic steatosis have focused largely, though not exclusively, on (1) reducing substrate availability to the liver, (2) reducing hepatic lipid synthesis, and (3) increasing hepatic mitochondrial fat oxidation (Figure 1). This Perspective will discuss these three classes of emerging pharmacologic therapies against hepatic steatosis, with the ultimate intent to ameliorate NAFLD and/or nonalcoholic steatohepatitis, and the advantages and pitfalls afforded by each strategy to treat these epidemics of obesity‐associated liver disease.